Nebel, Lufthaushalt und Lufthygiene im Alpenraum.: Ein Beitrag der Fernerkundung zur Gebirgsklimatologie - Winiger, Matthias; Bachmann, Matthias; Bendix, Jörg (ERDKUNDE, 1992)
The operational use of meteorological satellite data in boundary layer meteorology and climatology is still rather limited compared to the synoptic or global scale. Especially in mountain areas where most meteorological parameters significantly vary within short distances satellite data can improve the quality of investigations. For the spatial evaluation of fog layers and their physical properties, as well as for fog climatology in the Alpine foreland procedures based on digital NOAA-A VHRR data and results are presented: (1) The discrimination of fog and other surfaces by means of a threshold technique (temperature difference between channel 4 and channel 3). (2) By the superposition of a data set with the coordinates of the fog boundary and a digital elevation model the elevation of the upper fog limit can be determined. (3) Visibility and liquid water content of the fog layer highly correlate with the daytime signal of channel 3 (3.7 p.m). (4) Regional aspects of horizontal flow patterns and air mass exchanges in the boundary layer are evaluated by a combined use of a mesoscale model and the respective satellite data. Based on a climatological satellite data set, maps of the following climatological phenomena far the Swiss Plateau and the Po Valley have been produced and are discussed in the paper: Spatial distribution and frequency of the fog layers, frequency of their marginal position, fog persistence, visibility and liquid water content as well as potential risk of immission due to damp deposition.